2006
DOI: 10.1080/14734220600930588
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar efferent neurons in teleost fish

Abstract: In tetrapods, cerebellar efferent systems are mainly mediated via the cerebellar nuclei. In teleosts, the cerebellum lacks cerebellar nuclei. Instead, the cerebellar efferent neurons, termed eurydendroid cells, are arrayed within and below the ganglionic layer. Tracer injections outside of the cerebellum, which retrogradely label eurydendroid cells demonstrate that most eurydendroid cells possess two or more primary dendrites which extend broadly into the molecular layer. Some eurydendroid cells mostly situate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 55 publications
4
59
0
Order By: Relevance
“…Detection of nNOS in eurydendroid cells of masu salmon cerebellum confirms received our earlier data on histological labelling of NADPH-d in the neurons of this type of fish [46]. According to Ikenaga with co-authors [47], most of the eurydendroid cells in fish are aspartat-ergic and receive GABA-ergic impulses from the Purkinje cells. According to our data, the population of eurydendroid cells of masu salmon in cerebellum contains GABA-ergic and PA-ergic cells.…”
Section: +supporting
confidence: 69%
“…Detection of nNOS in eurydendroid cells of masu salmon cerebellum confirms received our earlier data on histological labelling of NADPH-d in the neurons of this type of fish [46]. According to Ikenaga with co-authors [47], most of the eurydendroid cells in fish are aspartat-ergic and receive GABA-ergic impulses from the Purkinje cells. According to our data, the population of eurydendroid cells of masu salmon in cerebellum contains GABA-ergic and PA-ergic cells.…”
Section: +supporting
confidence: 69%
“…In the granule cell layer, synaptic interactions occur among mossy fibers, granule cells, and Golgi interneurons in the cerebellar glomeruli. Eurydendroid cells are located in the vicinity of the Purkinje cell layer, contact Purkinje cell axons, and send their axons through the granule cell layer to different areas outside the cerebellum in teleost (Murakami and Morita, 1987;Folgueira et al, 2006;Ikenaga et al, 2006).…”
Section: Anatomy Of the Cerebellummentioning
confidence: 99%
“…These cerebellar eurydendroid cells are thought to perform functions similar to those of deep cerebellar nuclei neurons in tetrapods (Finger, 1978;Ikenaga et al, 2006). A recent in situ hybridization study (Toscano-Márquez et al, 2013) showed that M3 is the only muscarinic receptor present in the ELL and that its mRNA is homogenously distributed across pyramidal cells in all three tuberous ELL segments (Fig.2A) et al, 2013).…”
Section: Distribution Of Cholinergic Input To Ell Pyramidal Cellsmentioning
confidence: 99%